Essential Thrombocythemia and Epidural Analgesia in the Parturient: Does Thromboelastography Help?. Issue 6 (November 1996) - Lowenwirt, I.; Dadic, P.; Krishnamurthy, V.
Abstract : Background and Objectives: It is often considered that essential thrombocythemia contraindicates placement of an epidural catheter because of the danger of epidural hematoma. Thromboelastography offers a possible means of determining the appropriateness of epidural analgesia in a patient with this disorder. Methods: A pregnant woman with essential thrombocythemia and a history of spontaneous abortions was evaluated by thromboelastography at 38 weeks of gestation to determine the safety of using epidural analgesia for labor pain management. On the basis of the thermoelastography findings, the patient was given epidural analgesia with bupivacaine and fentanyl during her labor. Results: The patient experienced good pain relief, delivered a healthy infant vaginally, and suffered no complications. Conclusions: Thromboelastography may be a useful diagnostic test in determining the suitability of regional techniques for labor analgesia in parturients with essential thrombocythemia. However, success in one patient does not prove the general safety of this approach.